Credit derivatives: Do they matter to avoid credit exposure? (Some evidences from the US market) - Alnassar W.I.; Chin O. (Serials Publications, 2023)
Credit derivatives (CDs) have been increasingly acknowledged as an important requirement to hedge and transfer credit risk CR. Nonetheless, they have been extensively criticized for destabilizing the whole economic system bringing about the latest subprime credit crisis. The studys main aim is to investigate the reason for the use of (CDs), whether it is used for hedging or trade purpose, for four of the US international financial institutions that had made it through the 2007 crisis to resume functioning post-crisis. This will be for three different and critical periods, namely the pre, during and after crisis periods (Q1, 2000-Q1, 2014). Adopting the SUR technique, the investigation of the factors that influence the net position of (CDs) as to achieve the main purpose is made possible. It has been found that the use of (CDs) is inconsistent with the predictions of theories of risk management to this day. The implication is that most derivatives positions are held for dealer activities rather than for loan hedging. Reflecting that financial institutions also resort to using (CDs) for trading and speculation, this provides an indication for a risk-taking motive. Entities that have a better position in regard of their size, capital and net interest margin make greater use of (CDs) for this purpose. Serials Publications Pvt. Ltd.